Left Ventricular Longitudinal Dyssynchrony by CMR Feature Tracking Is Related to Adverse Prognosis in Advanced Arrhythmogenic Cardiomyopathy - Song, Yanyan; Li, Lu; Chen, Xiuyu; Ji, Keshan; Lu, Minjie; Hauer, Richard; Chen, Liang; Zhao, Shihua (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Left ventricular (LV) involvement has been associated with unfavorable prognosis in arrhythmogenic cardiomyopathy (ACM). We aim to evaluate LV mechanics by Cardiovascular Magnetic Resonance-Feature Tracking (CMR-FT) in ACM patients with right ventricular (RV) dysfunction. Methods: We retrospectively recruited ACM patients diagnosed according to the revised Task Force Criteria (rTFC) from January 2015 to July 2017. All patients underwent CMR examinations and collections of clinical, electrocardiographic data. The strain and dyssynchrony parameters of LV and RV were analyzed. These patients were followed, and primary study outcome was defined as a composite of cardiovascular events (arrhythmic events and heart transplantation), secondary study outcome included arrhythmic events. Results: Eighty-nine ACM patients (40.40 ±13.98 years, 67.42% male) were included. LV and RV ejection fraction were 49.12±12.02% and 22.28±10.11%, respectively. During a median (IQR) follow-up for 18.20 (11.60-30.04) months, thirty patients experienced cardiovascular events which included twenty-two patients experienced arrhythmic events. Patients with cardiovascular events had impaired LV global longitudinal strain (-10.82 ± 2.77 vs -12.61 ± 3.18%, p=0.010), impaired LV global circumferential strain (-11.81 ± 2.40 vs -13.04 ± 2.83%, p=0.044) and greater LV longitudinal dyssynchrony (LVLD) (80.98 ± 30.98 vs 64.23 ± 25.51 ms, p= 0.012) than those without. After adjusting for age, sex and other confounding factors, LVLD ≥89.15 ms was an independent risk factor for cardiovascular events (HR: 4.50, 95% CI: 1.94 to 10.42 ; p =0.001) and for arrhythmic events (HR: 4.79, 95% CI: 1.74 to 13.20; p = 0.003). Conclusions: LVLD by CMR-FT was an independent risk factor for cardiovascular and arrhythmic events in ACM patients in advanced stage, which could provide prognostic value for this subtype.